Effect of different electron acceptors on Enhanced Biological Phosphorus Removal (EBPR) systems in tropical climates - Oh, James Yong Jun (2018)
Previous studies on lab-scale nitrite EBPR systems had shown great success in simultaneous phosphorus and nitrogen removal. The viability of nitrite EBPR systems opens new possibilities in a real wastewater treatment plant such as implementing nitritation to convert ammonium into nitrite and subsequently reduce nitrite coupled with P uptake which could potentially reduce cost through reduced aeration and sludge wastage. However, nitrous oxide production, a potent greenhouse gas, is commonly associated nitritation and nitrite EBPR systems. Previous studies had suggested that using internal carbon sources such as PHA could have led to nitrous oxide accumulation due to the slower rate of electron release as compared to external carbon sources. This study is separated into two parts. The 1st part investigates the potential of phosphorus uptake under anoxic conditions using nitrite and nitrate as electron acceptors and acetate, propionate or mixed feed as the carbon source. Two sequencing batch reactors, SBRNO2 and SBRNO3, were inoculated with clade II PAOs from a parent reactor and were acclimatized with nitrite and nitrate respectively. Long-term operations of SBRNO2 and SBRNO3 showed that nitrite was more efficient as compared to nitrate for P uptake by PAOs and the use of acetate resulted in a better anoxic P removal activity as compared to propionate. The 2nd part investigates the nitrous oxide accumulation during endogenous denitrification in DPAO and DGAO enriched culture under various feed sources. Three separate 2 L reactors were used to cultivate Accumulibacter, Competibacter, and Defluviicoccus. Batch tests were conducted using various electron acceptor addition schemes after long-term enrichment. Preliminary results also showed no nitrous oxide accumulation for PAO reactors under acetate conditions, while slight nitrous oxide accumulation was observed under propionate conditions. DGAOs enriched under acetate had higher affinity towards reducing nitrous oxide while DGAOs enriched under propionate had lower affinity towards reducing nitrous oxide. The cooperation between DGAOs and DPAOs could have resulted in complete denitrification under acetate conditions despite the use of internal carbon sources.